Epidemiology of multiple myeloma in Taiwan, a population based study. (August 2018) - Tang, Chao-Hsiun; Liu, Hung-Yi; Hou, Hsin-An; Qiu, Hong; Huang, Kuan-Chih; Siggins, Sarah; Rothwell, Lee Anne; Liu, Yanfang
Highlights: Between 2007–2012 the age-adjusted incidence of MM in Taiwan increased by 13%. In parallel, case fatality decreased from 25.5% to 19.4%. The use of bortezomib, thalidomide, and lenalidomide in MM has increased steadily. MM remains largely incurable with high mortality. Abstract: Background: Although the incidence of multiple myeloma (MM) in Asia is lower than in Western countries, it is steadily increasing. However, limited data are available that describe the epidemiology of MM in Asia. Methods: We conducted a retrospective cohort study using the Taiwan National Healthcare Insurance Research database to estimate the disease burden and clinical characteristics of patients with MM in Taiwan. All newly diagnosed confirmed MM patients during 2007–2012 were enrolled. Patients were followed up until death or end of the observation period (December 31, 2013), whichever occurred first. Results: A total of 2723 newly diagnosed MM patients were included in the cohort analysis, of whom 58.0% (1578/2723) were men. The average age of MM patients was 67.6 years. At the time of diagnosis, the mean Charlson Comorbidity Index was 1.8, 35.3% of patients had anemia, 18.0% had bone fracture, 16.4% had renal disease and 17.3% had pneumonia. The crude annual incidence of newly diagnosed MM increased from 1.74 per 100 000 population in 2007 to 2.27 per 100 000 population in 2012 (p < 0.0001), and the age-adjusted incidence from 1.41 to 1.59 per 100 000 population (p = 0.01). The use of novel treatments expanded over the study period. The crude and age-adjusted annual MM mortality rate did not change significantly over time. Case fatality decreased from 25.5% in 2007 to 19.4% in 2012 (p < 0.0001). Conclusion: The age-adjusted incidence of MM in Taiwan increased by 13% between 2007 and 2012. Despite the introduction of new treatments, MM remains largely incurable with 19.4% mortality.